PENGARUH FASILITAS DAN LOKASI TERHADAP MINAT BERKUNJUNG PADA WATER BOOM AREMA RAYA KOTA BIMA - Awal Awaluddin; Intisari Haryanti (MANAJEMEN DEWANTARA, 2021)
Satisfying consumer needs is the dream of every company. Apart from being an important factor for the company's survival, meeting consumer needs can increase its superiority in competition. Consumers who are satisfied with the facility and location tend to buy back the product and reuse the product when the same needs reappear at a later date. This study aims to determine the effect of facilities and location on the interest in visiting the water boom arema raya bima city. This study uses a quantitative approach with a survey method, while this type of research includes associative research. The population in this study were consumers who had visited the Araema Raya water boom, the number of samples taken in this study were 100 respondents. The sample used in this study was purposive sampling. The research instrument used a questionnaire with a Likert scale. Data analysis used multiple linear regression, correlation test, determination test, partial test analysis with t test and f test (simultaneous). To test the effect between variables using SPSS (Statistical Service Product Solutions) version 26.00. The results of the study based on the t test (partial) show that there is no effect of facilities on interest in visiting, location has an effect on interest in visiting, while facilities and location jointly affect interest in visiting. Keywords: Facilities, Location, Visiting Interest